2007
DOI: 10.1090/s0025-5718-07-02047-9
|View full text |Cite
|
Sign up to set email alerts
|

An $hp$-local discontinuous Galerkin method for some quasilinear elliptic boundary value problems of nonmonotone type

Abstract: Abstract. In this paper, an hp-local discontinuous Galerkin method is applied to a class of quasilinear elliptic boundary value problems which are of nonmonotone type. On hp-quasiuniform meshes, using the Brouwer fixed point theorem, it is shown that the discrete problem has a solution, and then using Lipschitz continuity of the discrete solution map, uniqueness is also proved. A priori error estimates in broken H 1 norm and L 2 norm which are optimal in h, suboptimal in p are derived. These results are exactl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 19 publications
(26 reference statements)
1
26
0
Order By: Relevance
“…(5.19) Since [[φ]] = 0 on Γ I and φ = 0 on boundary of Ω, we rewrite the second term on the right-hand of (5. 19) as…”
Section: Postprocessing Of U H and Superconvergence Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(5.19) Since [[φ]] = 0 on Γ I and φ = 0 on boundary of Ω, we rewrite the second term on the right-hand of (5. 19) as…”
Section: Postprocessing Of U H and Superconvergence Resultsmentioning
confidence: 99%
“…It is again observed in [9] that if C 11 and C 22 are of order one, then u h and q h converge in L 2 -norm with order k + 1 and k + 1/2, respectively, for any k ≥ 0. Subsequently, the authors in [19] have discussed the LDG method for quasilinear elliptic boundary value problems and they have shown that u h and q h converge in L 2 -norm with order k + 1 and k, respectively. For the LDG method applied to nonlinear elliptic problems, we also refer to [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a review of work on DG methods for elliptic problems, we refer to [3,31]. [12][13][14] discuss DG methods for quasilinear and strongly non-linear elliptic problems. In [33,34], a non-symmetric interior penalty DGFEM is analyzed for elliptic and non-linear parabolic problems, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In [5], optimal order of convergence of LDG method applied to a Poisson equation has been established. Subsequently, Perugia and Schötzau [18] have discussed a priori hp-error estimates for linear elliptic problems and then, Gudi et al [12] have derived hp-error estimates for nonlinear elliptic problems. For higher order partial differential equations using LDG method, see [7,9,13,25,26] and references, therein.In this paper, hp-DG methods which, in particular, include the original LDG scheme, are applied to the problem (1.1)-(1.4).…”
mentioning
confidence: 99%